Strategic Analysis of Ambient Dairy and Non Dairy Product Portfolio of Gujarat Dairy Cooperatives - , Mahendra D. Gurjar, Pramith U Don, Zeel Modi (Archives of Current Research International, 2025)
The aim of present study is to analyse the vast ambient product portfolio of Gujarat’s dairy cooperatives, with a primary focus on the Gujarat Cooperative Milk Marketing Federation (GCMMF) and its flagship brand, Amul. The Gujarat Dairy Cooperatives is a globally recognized model for farmer-owned and controlled dairy businesses. It has significantly impacted the state's economy and rural livelihoods. The cooperative structure, spearheaded by Amul, has fostered the "White Revolution" in India, making the country the world's largest milk producer. Since a long time it has maintained it dominance in Dairy Sector. One of the main strength of the organization is ability to go for “Related Diversification” which enables it to leverage existing resources, capabilities, and customer base. Amul has expanded its portfolio in vast dairy as well as non-dairy products (such as Bakery, Chocolates, Organic and so on). The study investigates the strategic diversification of Amul’s product range across multiple categories—including ghee, milk powder, protein beverages, spreads, bakery items, chocolates, organic and health-focused foods—designed to meet evolving consumer preferences, nutritional demands, and market trends. Through a product-centric analysis, the study examines variant types, packaging, shelf life, functional benefits, and market reach, particularly in general and modern trade formats. The study indicates that Gujarat Dairy Cooperatives, under the Amul brand, have developed a comprehensive and diversified product portfolio of ambient offerings that cater to a wide demographic — from infants to fitness enthusiasts. The Key findings indicate that GCMMF has -Breadth and depth of portfolio across ghee, milk powders, beverages, proteins, chocolates, bakery, and organic products, Strategic alignment with health and wellness trends, such as lactose-free drinks, high-protein products, and sugar-free cookies, Use of ambient packaging formats (tetrapak, PET bottles, cans) to enhance shelf life and convenience, and Multi-channel distribution through General Trade (GT), Modern Trade (MT), e-commerce, and institutional sales, enabling wide accessibility. As a result, it attempts leverage its existing brand and customer base. Further its vast product portfolio exhibits the strong Research and Development capabilities with respect to Product. The product strategy is holistic, integrating nutrition, affordability, tradition, and innovation, thereby cementing Amul’s role as not just a dairy leader but a complete food solutions provider in India and select global markets.